Gambaran Status Gizi Kurang Berdasarkan Bb/U Pada Anak Tahun Di Puskesmas X, Kabupaten Tangerang Tahun 2025 - Inna Mukhaira; Indah Ratika Sari (JUMAGI (Jurnal Madani Gizi Indonesia), 2025)
ABSTRACT Children's nutritional status is an important indicator used to assess the health status of a population. One of the indicators used to measure children's nutritional status is weight-for-age (WFA). Nutritional problems in children, particularly underweight, remain a concern because they can affect children's growth and development. This study aimed to describe children's nutritional status based on the weight-for-age indicator in the working area of Puskesmas X, Tangerang Regency. This study used a descriptive analytic design with a quantitative approach. Secondary data were obtained from Posyandu records using a total sampling technique. The sample consisted of 179 children. Data were analyzed descriptively to describe the distribution of nutritional status based on sex and age. The results showed that most respondents were male (54.7%). The mean age of the children was 88.9 months, ranging from 6 to 157 months. Based on the weight-for-age indicator, most children were categorized as underweight (44.7%), followed by normal nutritional status (40.2%) and severely underweight (15.1%). Severely underweight status was more common among boys than girls. Therefore, regular growth monitoring through Posyandu activities and parental education regarding balanced nutrition need to be improved.